Saving, Investment, and the Regional Current Account : An Analysis of Canadian, British, and German Regions - Thomas, Alun. (Washington, D.C. : International Monetary Fund, 1993)
The relationship between regional saving and investment is examined to measure the extent of capital mobility. The relationship between total regional saving and investment is significantly negative in Canada and the United Kingdom, in contrast to the significant positive relationship found across countries. The difference is attributed to government subsidies to poor regions. The relationship between personal saving and private investment is insignificant in the U.K. and Germany and is negative in Canada which suggests that capital is mobile for individuals. The relationship between retained earnings and private investment is significantly positive in the U.K. and Canada suggesting capital immobility for firms but a test for the presence of regional corporate liquidity constraints yields no effects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet